2018
DOI: 10.1111/jon.12579
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Sonographic, and Electrophysiologic Longitudinal Features of Chronic Inflammatory Demyelinating Polyneuropathy

Abstract: BACKGROUND AND PURPOSE Several studies have aimed to find potential biomarkers to simplify the diagnosis of chronic inflammatory demyelinating polyneuropathy (CIDP) and to monitor and predict the disease course. However, reliable markers are still lacking. We aimed to investigate whether high‐resolution nerve ultrasound (HRUS) is suitable for monitoring the long‐term clinical course of CIDP. METHODS Twenty patients fulfilling the definite diagnostic criteria of CIDP received clinical examination, evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
2
22
1
2
Order By: Relevance
“…Hartig et al showed that some patients developed progressive nerve enlargement despite clinical improvement or stabilization. Fisse et al showed that intranerve CSA variability of the tibial and fibular nerves but not the median and ulnar nerves increased with disease progression. Transverse images of the median and ulnar nerves were obtained at only 2 locations in these studies.…”
mentioning
confidence: 99%
“…Hartig et al showed that some patients developed progressive nerve enlargement despite clinical improvement or stabilization. Fisse et al showed that intranerve CSA variability of the tibial and fibular nerves but not the median and ulnar nerves increased with disease progression. Transverse images of the median and ulnar nerves were obtained at only 2 locations in these studies.…”
mentioning
confidence: 99%
“…However, nerve conduction studies cannot reproduce clinical dynamics, i.e. due to severe secondary axonal damage [23]. Studies on use of electromyography for disease monitoring are lacking.…”
Section: The Challenge Of Clinical and Electrophysiological Monitoringmentioning
confidence: 99%
“…In disease course, increase or decrease of CSA enlargement, i.e. measured by intra-nerve CSA variability, can provide information about disease activity and response to therapy [23,41].…”
Section: Nerve Ultrasoundmentioning
confidence: 99%
“…Over the years, it has evolved into a distinct ultrasound subspecialty. A vast amount of literature provides evidence regarding the value of neuromuscular ultrasound in the diagnostic evaluation of neuromuscular disorders (more key references are provided in Data S1 online) . As a result, neuromuscular ultrasound has become a fundamental diagnostic tool in many electrodiagnostic labs, clinics, and radiology centers.…”
Section: Introductionmentioning
confidence: 99%
“…vided in Data S1 online). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] As a result, neuromuscular ultrasound has become a fundamental diagnostic tool in many electrodiagnostic labs, clinics, and radiology centers. This has driven a growing interest among physicians to learn and master the skill.…”
mentioning
confidence: 99%